Serine Metabolism Regulates YAP Activity Through USP7 in Colon Cancer - Zhao, Xiaoya; Fu, Jianfei; Hu, Bin; Chen, Lin; Wang, Jing; Fang, Jinyong; Ge, Chenyang; Lin, Haiping; Pan, Kailing; Fu, Liang; Wang, Lude; Du, Jinlin; et al. (Frontiers in Cell and Developmental Biology, 2021)
The metabolic reprogramming is a vital factor for the development of many type cancers, including colorectal cancer (CRC). Serine metabolic reprogramming is one of the prominent features of tumor metabolism. Yes-associated protein (YAP) participates in organ size control and tumorigenesis. However, the relationship between YAP and serine metabolism in CRC is unclear. In this study, RNA sequencing and metabolomics results represented significantly enriched glycine, serine and threonine metabolism pathways were significantly enriched in serine-starvation-resistant cells. Next, short-term serine deficiency inhibits YAP activation, whereas prolonged response in turn dephosphorylates and promotes YAP activity. Mechanistically, USP7 strengthen YAP stability under increased serine condition by regulating deubiquitinating. More interestingly, Verteporfin (VP) could effectively inhibit the proliferation of CRC both in cells and organoids, and even could modulate serine metabolism by reversely impeding USP7 expression. Clinically, YAP was significantly activated in colon tumor tissues and positively correlated to phosphoglycerate dehydrogenase (PHGDH) and USP7 expression. Our study uncovered the mechanisms by which serine metabolism regulates YAP via USP7 and identified the crucial role of YAP in regulating cell proliferation and tumor growth, and implied VP may provide a new idea for the treatment of CRC.